Management of childhood Gitelman syndrome: a case study - Risky Vitria Prasetyo; Putu Dian Saraswati; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer (Indonesian Pediatric Society, 2016)
Gitelman syndrome is a rare, autosomal recessive, renal tubular salt wasting disorder characterized by hypokalemia, and metabolic alkalosis in combination with significant hypomagnesemia and hypocalciuria.1,2 The prevalence is estimated to be 1 in 40,000 individuals. The condition affects both males and females of all ethnic backgrounds. The prevalence of heterozygotes is approximately 1% in Caucasian populations.2,3In the majority of cases, symptoms do not appear before the age of six years and the disease is usually diagnosed during adolescence or adulthood. Symptoms, such as transient episodes of muscle weakness and tetany, sometimes accompanied by abdominal pain, vomiting and fever, are often seen in Gitelman syndrome patients. Paresthesias, especially in the face, frequently occur. Remarkably, some patients are completely asymptomatic except for the appearance of chondrocalcinosis at adult age that causes swelling, local heat, and tenderness over the affected joints. Blood pressure is lower than that in the general population. Sudden cardiac arrest has been reported occasionally. In general, growth is normal but can be delayed in those Gitelman syndrome patients with severe hypokalemia and hypomagnesemia.2,4